Analysis on the Implementation of Role-playing in English for Tourism Services - Milawaty Milawaty (P3M Politeknik Negeri Jember, 2022)
Communicating in English is crucial for tourism services, considering that the tourists who visit tourism destinations are not only originated from the country (domestic tourists), but also from the overseas (foreign tourists). For this reason, learning English for tourism services needs to be conducted especially by the students of Tourism Destination Study Program to improve their English speaking skill. To provide a maximum result in improving the students’ English speaking skill, role-playing is an alternative activity to be conducted in the classroom. Therefore, the author implemented the role-playing activities for a period of time. To investigate how well the implementation went, an analysis was conducted. Unfortunately, from the analysis, it was realized that the implementation of role-playing still showed non-optimal results. By employing SWOT analysis, it could be concluded that the implementation of role-playing had some strengths, including the high student participation, the improvement of English communication skill, a deeper material comprehension through simulation, as well as the enrichment of English vocabulary. However, some weaknesses were also found, including the difficulty of the students in memorizing all the text, the grammatical errors, the pronunciation mistakes and the lack of fluency due to environmental factor. It was added with some threats preventing the optimal implementation, such as the lack of determination in conducting the activity in the class, the students’ low motivation, the unprepared performance, as well as the lack of time to practice. Yet, role-playing still had the opportunity to be well implemented in English for tourism services since it provides a fun and interesting way of learning. Hence, those obstacles in implementing role-playing shall be overcome to increase the students’ English speaking skill in the future.